E-095 Early Hyperglycemia Predicts Poor Outcome Despite Successful Stroke Thrombectomy. (29th July 2016) - Dezse, K; Bajgur, S; Harrison, A; Mejilla, J; Hicks, W; Davis, T; Pema, P; Budzik, R; Vora, N
Abstract : Objective: Our goal was to identify medical co-morbidities which negatively prognosticate outcome in stroke patients who have successful endovascular reperfusion after imaging-based selection. Methods: With approval, we retrospectively reviewed stroke interventions in the intracranial carotid and M1 middle cerebral artery at our institution over a two year period. All patients are screened for small infarcts based on a non-contrast head CT and perfusion imaging for treatment eligibility. For analysis, we included those patients with successful reperfusion only. We collected stroke risk factors, time to treatment, stroke scale, and additional medical co-morbidities: cardiomyopathy, chronic lung disease, chronic kidney disease, body mass index >30, early hyperglycemia (any 24 hour post-procedure blood sugar >150 gm/dl), history of malignancy, and dementia. These co-variates were placed into a univariate analysis to identify predictors for a poor outcome, defined as a modified Rankin Scale >2 at 90 days. Covariates with a p value of <0.2 were included in a multiple logistic regression model to identify independent predictors. Results: We analyzed 120 patients with mean age 70 (SD 13) years, median NIHSS 16, and mean time to reperfusion 408 (SD 345) minutes. Poor outcome was seen in 44 patients (37%) with mortality in 21 patients (17.5%). After controlling for age and stroke score, early hyperglycemia was the only co-variate independently associated with poor outcome (OR 2.72, 95% CI 1.04–7.06, p = 0.04) and mortality (OR 3.18, 95% CI 1.28–7.86, p = 0.013). Conclusions: In selected stroke patients with successful endovascular reperfusion, early hyperglycemia may be independently associated with poor outcome and mortality over other medical co-morbidities. Further prospective study confirming this effect may further develop treatment strategies to prevent this injury. Disclosures: K. Dezse: None. S. Bajgur: None. A. Harrison: None. J. Mejilla: None. W. Hicks: None. T. Davis: None. P. Pema: None. R. Budzik: None. N. Vora: 2; C; Medtronic Neurovascular, Microvention Neurovascular. 3; C; Medtronic Neurovascular.